Jagdish, Son of Ahmad: Dalit Religion and Nominative Politics in Lucknow - Joel Lee (South Asia Multidisciplinary Academic Journal)
Between the late 1940s and the 1970s, the sanitation labour castes of Lucknow radically altered their nominative practices, replacing Islamicate personal names with names in a Hindu style, and abandoning the caste title Lal Begi in favor of the surname Valmiki. Based on oral histories and ethnographic research with the Valmiki community in Lucknow, the article presents and evaluates evidence for how and why this transformation took place. Building on Nicolas Jaoul’s (2011: 280) insight into the ‘politically engineered’ nature of the consolidation of the sanitation labour castes under the sign of a Hindu sage, the article argues that Congress policy at the national level played a decisive role in the renaming of an entire swath of the Dalit population. At the same time, working with Ambedkar’s assessment of the Valmiki movement as ‘clandestine conversion’ and ‘undergoing protective discolouration,’ it is argued that the nominative Hinduization of the sanitation labour castes may not constitute the Hindu majoritarian triumph that it appears to be.